Incidence of ISO 9001 certification in business results. A colombian case (2018)
This research is focused on establishing the impact generated by the implementation and certifi cation of ISO 9001 in some companies in the department of Boyaca - Colombia. For evaluating a representative sample of those with active certifi cation and at least two years old is taken; they were given a form that collects information related to the performance of organizations in various aspects. Finally, by applying statistical analysis techniques certifi cation incidence was assessed. We concluded that the eff orts of companies to achieve certification of ISO 9001 cause a positive impact on performance, specifi cally in areas such as process improvement, product planning and design, and customer satisfaction. The research aims to help practitioners of quality management to understand more the possible consequences of the implementation and certification of a quality management system under ISO 9001.